2020
DOI: 10.3390/ijfs8010005
|View full text |Cite
|
Sign up to set email alerts
|

Key Audit Matters for Production-To-Order Industry and Conservatism

Abstract: In this study, the effects of key audit matters (KAMs), one of the measures recently introduced to improve accounting transparency in the production-to-order industry in terms of corporate sustainability, are examined. After the introduction of KAMs, auditors should publicly disclose key audit matters that had been internally judged in the past. In cases where these are missing or misunderstood, the range of the auditor’s liability may increase. Thus, from the viewpoint of the auditor, the description of KAMs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Simnett and Huggins (2014) found that, overall, there was a high level of support from stakeholders to the changes to the audit report proposed by the IAASB (2012). Regarding the KAMs, or the PCAOB critical audit matters (CAMs), they may lead to an improvement of financial reporting quality (Gold et al 2020;In et al 2020). However, it is not fully determined by academia, if they close the information gap, or even if they significantly affect investors' reactions, although they give users some of the information demanded (Brasel et al 2016;Christensen et al 2014;Gutierrez et al 2018;Moroney et al 2020;Velte and Issa 2019).…”
Section: Efforts To Increase the Value Of Audit Reports By Changing Their Content And Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Simnett and Huggins (2014) found that, overall, there was a high level of support from stakeholders to the changes to the audit report proposed by the IAASB (2012). Regarding the KAMs, or the PCAOB critical audit matters (CAMs), they may lead to an improvement of financial reporting quality (Gold et al 2020;In et al 2020). However, it is not fully determined by academia, if they close the information gap, or even if they significantly affect investors' reactions, although they give users some of the information demanded (Brasel et al 2016;Christensen et al 2014;Gutierrez et al 2018;Moroney et al 2020;Velte and Issa 2019).…”
Section: Efforts To Increase the Value Of Audit Reports By Changing Their Content And Formmentioning
confidence: 99%
“…In future studies, it would be interesting to examine whether the reason for the higher value attached by users than by auditors lies in the fact that users' answers could be given without cost considerations or other reasons. It would also be interesting to study whether the lower value given by auditors was a consequence of the increase in auditors' perceptions of litigation risks associated with the new disclosures (Gimbar et al 2016;In et al 2020).…”
Section: Rq2: Content Of Audit Reports To Enhance Their Value For Decision Makingmentioning
confidence: 99%
“…From another perspective, studies such as those of Alves and Galdi (2020), In et al (2020), Reid et al (2019), andSantos et al (2020) have sought to analyze the empirical implications of KAMs for the capital market. Alves and Galdi (2020) observed that there is a positive association between the adoption of NBC TA 701 and share price behavior.…”
Section: Previous Evidence and Development Of The Hypothesesmentioning
confidence: 99%
“…Alves and Galdi (2020) observed that there is a positive association between the adoption of NBC TA 701 and share price behavior. In turn, In et al (2020), Reid et al (2019), andSantos et al (2020) presented initial evidence that the adoption of the standard has worked to discourage earnings management practices.…”
Section: Previous Evidence and Development Of The Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation